Willingness to Pay for COVID-19 Vaccines in Indonesia: A Thematic Analysis: [Kesediaan Membayar Untuk Vaksinasi COVID-19 di Indonesia: Studi Analisis Tematik] - Adelina, Shella; Sekarasih, Laras (ANIMA Indonesian Psychological Journal, 2023)
During the pandemic, the Indonesian government has striven to implement steps to prevent and control the impacts of COVID-19, one of which is through a free program of vaccinations, from the first to the third dose (booster), in order to raise herd immunity. Although these were free, the take-up of the booster vaccination has been slow. This study was aimed at exploring individual preparedness to pay for COVID-19 vaccination, if the government was no longer to pay for these vaccines. The study was conducted using a quantitative approach, employing thematic analysis techniques. The participants comprised 27 people, with their ages ranging from 18-83 years. The results of the study found there were two principle themes (or factors) influencing the preparedness to pay for vaccinations, those of: (1) drive; and (2) deterrent. The drive factor comprised the aspects which supported the public in being prepared to receive, and pay for, vaccinations; these being the obligations to adhere to the regulations of government and institutions, to receive social assistance (welfare), and to ensure personal protection. The deterrent factor comprised the aspects which made the public reluctant to pay for the vaccinations, amongst others being the framing of information about the side-effects of the vaccine, the non-halal (religiously acceptable) composition of the vaccine, and the feeling of satisfaction after having received two doses. Amongst all of these factors, the obligatory nature of vaccination was the aspect most influencing the preparedness to pay. This study provides a picture of why the public may be prepared to pay for the vaccine, the factors which may elevate and depress their preparedness to pay, and thoughts about the costs of the vaccine, which may be the benchmarks in planning policies related to health behavior. The plans of the government to make COVID-19 vaccination subject to payment require assessment of the cost of the vaccine, because this will influence the number of members of the public who are prepared to pay to receive vaccination. This may certainly influence the level of public immunity to COVID-19, in the long term. Selama pandemi, pemerintah Indonesia berupaya melakukan pencegahan dan penanganan dampak COVID-19, salah satunya melalui program vaksinasi gratis dari dosis pertama hingga dosis ketiga (booster) untuk meningkatkan herd immunity. Meskipun gratis, laju vaksinasi booster lambat meningkat. Studi ini bertujuan untuk mengeksplorasi kesediaan individu untuk membayar vaksin COVID-19 jika pemerintah tidak lagi membiayai vaksinasi COVID-19. Studi dilakukan dengan pendekatan kualitatif dengan teknik analisis tematik. Partisipan terdiri dari 27 orang dengan rentang usia antara 18-83 tahun. Hasil studi ini menemukan dua tema utama yang memengaruhi kesediaan membayar vaksin: (1) faktor pendorong (drive); dan (2) faktor penghalang (deterrent). Faktor pendorong (drive) terdiri dari aspek yang mendorong masyarakat untuk bersedia mendapat dan membayar vaksin, yaitu kewajiban untuk mengikuti aturan pemerintah dan institusi, mendapatkan bantuan sosial, dan untuk perlindungan diri. Faktor penghalang (deterrent) merupakan aspek yang membuat masyarakat enggan membayar vaksin, antara lain framing informasi efek samping vaksin, komposisi vaksin yang tidak halal, dan merasa puas dengan dua dosis. Di antara seluruh faktor tersebut, kewajiban vaksinasi adalah aspek yang paling memengaruhi kesediaan membayar. Studi ini memberikan gambaran mengapa masyarakat bersedia membayar untuk vaksin, faktor yang dapat meningkatkan dan menurunkan kesediaan mereka untuk membayar vaksin, dan perkiraan harga vaksin COVID-19 yang dapat menjadi tolok ukur dalam merancang kebijakan terkait perilaku kesehatan. Rencana pemerintah untuk menjadikan vaksinasi COVID-19 sebagai vaksinasi berbayar membutuhkan asesmen mengenai harga vaksin karena akan memengaruhi seberapa banyak masyarakat yang bersedia untuk mengeluarkan biaya sendiri demi mendapatkan vaksinasi. Hal ini tentu dapat memengaruhi tingkat kekebalan masyarakat melawan COVID-19 dalam jangka panjang.